Rancang Bangun Alat Monitoring Daya Listrik di Asrama Berbasis Web Menggunakan ESP32 - Tresna Umar Syamsuri; Rahma Nur Amalia; Mudjiono; Aly Imron (Elposys: Jurnal Sistem Kelistrikan, 2022)
This study aims to design and build tools that can measure current, voltage, and electricity in the dormitory using a current sensor and voltage sensor controlled by a microcontroller. This device can be monitored and controlled on a real-time scale through the Blynk website and displayed through the LCD size. The tools that were built were placed centrally in the dormitory. Through the Blynk website, the dormitory owner gets the authority to determine the limit of the use of electricity in a room and increase the number of rooms as much as needed, while the room owner can monitor the mutation of electricity use. Every time the total power reaches the upper limit, relay will be active to decide on the electric current. This device is expected to be able to help the homeowner of the dormitory in calculating the cost of monthly electricity tokens. The simulation is carried out using a dormitory house model consisting of three rooms with a maximum power of 500 VA per room. Load simulation using lamps, fans, laptops, etc. The test results show a difference in sensor accuracy. The current sensor ACS712 in room 1 has a percentage of error of 11.88%, room 2 has 10.63%, and room 3 has 9.38%. Three ZMPT101B voltage sensors, considered quite accurate with a percentage of error 0.16%. So that the power value obtained has a percentage of power error for room 1 has 24.30%; Room 2 has 13.24%; While room 3 has 18.76%.